Phytochemical Study of Flavonoid "Casticin" Present in the Fruits of Vitex agnus-castus L. Cultivated in Iraq - Aous A. Shakir; Zainab J. Awad (College of Pharmacy University of Baghdad, 2017)
This study detects the presence of an important flavonoid "Casticin" in the fruits of Vitex agnus-castus L. grown in Iraq. The pharmaceutical importance of Casticin arise from its consideration as anti-tumor substance and have cytotoxic effects, and the absence of any study concerning Casticin content of this medicinal plant in Iraq, gave this study its importance. This study concerned with the extraction, identification, isolation and purification  of Casticin from the fruits of Vitex agnus-castus L. The extraction of this compound was carried out using  two methods. Identification of this compound was done by Thin Layer Chromatography (TLC) in which three different solvent system has been tried. This identification was further augmented by using High Performance Liquid Chromatography (HPLC) and then this compound was isolated and purified. Identification of the isolated Casticin was carried out using melting point (M.P.), Thin Layer Chromatography (TLC), and Infrared spectroscopy (IR). This study confirms the presence of Casticin in the fruits of  Vitex agnus-castus L. grown in Iraq. Key words : Vitex agnus â€" castus , Flavanoid , Casticin